2018
DOI: 10.1155/2018/9407971
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of the Association between Autoantibodies and Qualitative Ultrasound Index of Bone in an Elderly Sample without Clinical Autoimmune Disease

Abstract: Bone loss is characteristic of the ageing process and a common complication of many autoimmune diseases. Research has highlighted a potential role of autoantibodies in pathologic bone loss. The confounding effects of immunomodulatory drugs make it difficult to establish the contribution of autoantibodies amongst autoimmune disease sufferers. We attempted to examine the relationship between autoantibodies and bone mass in a population of 2812 elderly participants without clinical autoimmune disease. Serum sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 123 publications
0
6
0
Order By: Relevance
“…Thus, the NHANES data, although based on a limited number of autoantibodies, directly challenge assertions that autoantibodies are uncommon. In retrospect, these findings should not come as a surprise because, historically, both at the inception of early humoral autoimmunity studies and periodically thereafter, small-scale surveys using differing laboratory methodologies have shown similar results [71][72][73].…”
Section: Discussionmentioning
confidence: 78%
“…Thus, the NHANES data, although based on a limited number of autoantibodies, directly challenge assertions that autoantibodies are uncommon. In retrospect, these findings should not come as a surprise because, historically, both at the inception of early humoral autoimmunity studies and periodically thereafter, small-scale surveys using differing laboratory methodologies have shown similar results [71][72][73].…”
Section: Discussionmentioning
confidence: 78%
“…QUS is a noninvasive method for estimating bone mineral status of the peripheral skeleton. Dual-energy X-ray absorptiometry (DEXA) is currently considered the gold standard and comprises an accurate technique used to measure BMD at specific fracture-related sites, although QUS has been considered a valid and useful measure for determining bone health status in older people [ 77 , 78 , 79 ]. In addition to bone density, QUS provides some structural information that may be important in determining fracture risk [ 41 ] and identifying patients at risk of developing osteoporosis.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to bone density, QUS provides some structural information that may be important in determining fracture risk [ 41 ] and identifying patients at risk of developing osteoporosis. QUS offers wider accessibility because it is portable, easier to handle, lower in cost, and does not emit ionizing radiation [ 41 , 77 , 78 , 79 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is a safe, radiation-free modality that provides precise quantitative assessment of skeletal status, useful information in elderly for identifying patients at risk of developing osteoporosis and for assessing their risk of future fracture. [ 79 , 80 , 86 ] Bone mass we will measured at the calcaneus (95% of trabecular bone) by using QUS (Sahara Hologic Clinical Bone Sonometer; Hologic lnc., Waltham, MA). QUS parameters will be measured, but we consider the estimated BMD (g/cm 2 ) and T-score (comparison of the average mineral density of the patient's bone with a healthy young people) as primary outcome, because some researchers suggested that these parameters are more useful in the determination of subjects with low bone health status.…”
Section: Methodsmentioning
confidence: 99%
“…QUS parameters will be measured, but we consider the estimated BMD (g/cm 2 ) and T-score (comparison of the average mineral density of the patient's bone with a healthy young people) as primary outcome, because some researchers suggested that these parameters are more useful in the determination of subjects with low bone health status. [ 79 81 , 86 ]…”
Section: Methodsmentioning
confidence: 99%